A FERONIA-Like Receptor Kinase Regulates Strawberry (Fragaria × ananassa) Fruit Ripening and Quality Formation - Jia, Meiru; Ding, Ning; Zhang, Qing; Xing, Sinian; Wei, Lingzhi; Zhao, Yaoyao; Du, Ping; Mao, Wenwen; Li, Jizheng; Li, Bingbing; Jia, Wensuo (Frontiers in Plant Science, 2017)
Ripening of fleshy fruits is controlled by a series of intricate signaling processes. Here, we report a FERONIA/FER-like receptor kinase, FaMRLK47, that regulates both strawberry (Fragaria×ananassa) fruit ripening and quality formation. Overexpression and RNAi-mediated downregulation of FaMRLK47 delayed and accelerated fruit ripening, respectively. We showed that FaMRLK47 physically interacts with FaABI1, a negative regulator of abscisic acid (ABA) signaling, and demonstrated that FaMRLK47 regulates fruit ripening by modulating ABA signaling, a major pathway governing strawberry fruit ripening. In accordance with these findings, overexpression and RNAi-mediated downregulation of FaMRLK47 caused a decrease and increase, respectively, in the ABA-induced expression of a series of ripening-related genes. Additionally, overexpression and RNAi-mediated downregulation of FaMRLK47 resulted in an increase and decrease in sucrose content, respectively, as compared with control fruits, and respectively promoted and inhibited the expression of genes in the sucrose biosynthesis pathway (FaSS and FaSPS). Collectively, this study demonstrates that FaMRLK47 is an important regulator of strawberry fruit ripening and quality formation, and sheds light on the signaling mechanisms underlying strawberry fruit development and ripening.